Answer:
(14, 6 )
Explanation:
Given
x +
y = 3 ( multiply through by 42 to clear the fractions )
6x + 7y = 126 → (1)
x -
y = 5 ( multiply through by 6 to clear the fractions )
3x - 2y = 30 → (2)
Multiplying (2) by - 2 and adding to (1) will eliminate the x- term
- 6x + 4y = - 60 → (3)
Add (1) and (3)term by term to eliminate x
11y = 66 ( divide both sides by 11 )
y = 6
Substitute y = 6 into either of the 2 equations and evaluate for x
Substituting into (1)
6x + 7(6) = 126
6x + 42 = 126 ( subtract 42 from both sides )
6x = 84 ( divide both sides by 6 )
x = 14
Solution is (14, 6 )